Untangling the effects of climate variability and irrigation management on water levels in Lakes Titicaca and Poopó - Nilo Lima-Quispe; Marisa Escobar; Albertus J. Wickel; Manon von Kaenel; David Purkey (Journal of Hydrology: Regional Studies, 2021)
Study region: The catchment area of Lakes Titicaca and Poopó is located in the Peruvian-Bolivian Altiplano in the central Andes of South America. Study focus: We quantified the impact of irrigation and climate variability on the range of fluctuation of water levels in Lakes Titicaca and Poopó by applying the WEAP model to dynamically represents the hydrology of the catchment area, irrigation and water storage in the lakes. The model is implemented with observed climate datasets for the region, processed at a monthly time step for the historical period 1980–2015. New hydrological insights for the region: Fluctuations in water levels are mainly controlled by climate variability. Irrigation withdrawals aggravate unfavorable conditions, thus amplifying water level fluctuations. In Lake Titicaca the climate explains about 80 % of the fluctuation range and the remaining ∼20 % is due to irrigation. In Lake Poopó the role of climate also prevails with a contribution of about 65 %, while the remaining 35 % is attributed to irrigation. The difference in the relative contribution of irrigation between the lakes is due to the fact that the net inputs in Lake Poopó depend mostly on regional flows and on the contributions of Lake Titicaca; while in the much larger Lake Titicaca, there are net inputs due to precipitation on the lake surface in addition to the contributions of the tributaries.